Method of treating inflammatory disease with cardamonin - Israf Ali, Daud Ahmad; Lajis, Mohd Nordin; Ahmad, Syahida; Mohamad, Habsah (2011)

(untitled)
This invention relates to a method of treating inflammatory disease characterized by the production of an undesirable level on inflammatory mediators such as nitric oxide, thromboxane B₂ , prostaglandin E₂, or hydrogen peroxide. The method comprising of administering to a patient a pharmacologycal effective dose of cardamonin with a pharmaceutically acceptable carrier. The effective dose of cardamonin with a rage between about 0.02uM and 74 uM.